BOLD neurovascular coupling does not change significantly with normal aging. Issue 7 (17th April 2017) - Grinband, Jack; Steffener, Jason; Razlighi, Qolamreza R; Stern, Yaakov
Abstract: Studies of cognitive function that compare the blood oxygenation level dependent (BOLD) signal across age groups often require the assumption that neurovascular coupling does not change with age. Tests of this assumption have produced mixed results regarding the strength of the coupling and its relative time course. Using deconvolution, we found that age does not have a significant effect on the time course of the hemodynamic impulse response function or on the slope of the BOLD versus stimulus duration relationship. These results suggest that in cognitive studies of healthy aging, group differences in BOLD activation are likely due to age‐related changes in cognitive–neural interactions and information processing rather than to impairments in neurovascular coupling. Hum Brain Mapp 38:3538–3551, 2017 . ©2017 Wiley Periodicals, Inc.